KARAKTERISASI MINERAL PADA BATU GRANIT DI SEKITAR GUNUNG MARAPI DAERAH SUMATERA BARAT MENGGUNAKAN X-RAY DIFFRACTION (XRD) - Abdil Bajili (PILLAR OF PHYSICS, 2014)
Rock is a collection of one or more minerals which also becomes the main ingredient in the formation of the earth’s crust. The rock contains of important mineral which are widely utilized by humans in daily life and also it can be the basic ingredients for sector industry. West Sumatra is also rich of the natural sources inside the rocks in mineral form. Which is used by Seismic Method, concluded that one of the compiler layers of rock that dominated the earth’s crust in West Sumatra is granite rock. Granite is included in the type of intrusive igneous rock that process of coagulating take place under the surface of the earth and it comes out because the eruption of  volcano and the pressure in the earth.  West Sumatra is the province which has many active volcanoes, one of them is Marapi Mountain. Around the Marapi Mountain much by passed by the Fault Sumatran. So that the research purpose to determine the characterization of minerals in the granite rock surrounding Marapi Mountain using X-Ray Diffraction (XRD) and explore in West Sumatra have. X-Ray Diffraction (XRD) is the method needed to analyze mineralogy of a rock sample. The result found in the measurement is that there are Orthoclase, Quartz, Albite, Magnetite, Thorite, Ilmenite, Hornblende, Kaolinite, Muscovite, and Sodalite. With the value of susceptibility is 4,1 x 10-5 m3/kg, the value of density is 2,54 gr/cm3 and compress straight granite is 12,56 MPa. Keywords: Rock, mineral, West Sumatra, Marapi Mountain, Granite rock, X-Ray Diffraction (XRD).